Pork Barrel Politics: A Case Study of the Free Electricity Program in Aceh Jaya Local - Afrijal; Herizal; Saddam Rassanjani; Mukhrijal (Journal of Local Government Issues, 2024)
This study focuses on analyzing the practice of Pork Barrel Politics in the Free Electricity Program implemented by the Aceh Jaya local Government in 2014-2017. Providing free electricity is a flagship program spearheaded by the Regent of Aceh Jaya who is also the elite of the Aceh Party (PA) for underprivileged communities. The free electricity program has become a campaign tool and strategy for the local legislative representative incumbents who want to regain control of the Local House of Representatives in the 2014 Legislative Election. We took a qualitative approach using the case study method. Data collection used was through interviews, observation and documentation. The results of the research show that the implementation of the free electricity program assistance in Aceh Jaya was characterized by pork barrel political practices, where recipients of free electricity program in 2014-2017 were prioritized to people who were the Aceh Party members and supporters, the winning party in the 2014 Legislative Election. Pigs are inseparable from the participation of the Aceh Party elite who sit in executive positions and are supported by the dominance of Aceh Jaya DPRK members from the Aceh Party faction.